Schinkel 'in Athens' : meta-narratives of 19th-century city planning - Karidis, Dimitris N., (Archaeopress Publishing Ltd, 2022)
This text offers a fresh appraisal of Karl Friedrich Schinkel's urban design legacy and his involvement in the design of modern Athens in the 1830s. It challenges the common perception of Schinkel's proposed palace atop the Acropolis of Athens (1834) as a utopian scheme, detached from the realities of nineteenth-century Greece.